Triboelectric material of nano-porous composite fiber as well as preparation method and application of triboelectric material

The preparation of superhydrophobic nanoporous composite fiber membranes through electrospinning technology solves the challenges of friction nanogenerators in terms of durability and corrosion resistance, achieves high net friction charge density and excellent friction electrical properties, and is suitable for self-powered sensing and water wave energy collection.

CN119686028APending Publication Date: 2025-03-25BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411406163.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Friction nanogenerators face challenges in the development of blue energy, especially the disadvantages of poor breathability, easy debris and difficult processing of polymer materials have hindered their application.

Method used

A triboelectric material of one-step high-performance superhydrophobic nanoporous composite fiber is prepared by electrospinning technology, and a polyvinylidene fluoride and perfluoroethylene propylene copolymer nanoparticle spinning emulsion is used to form a porous composite fiber membrane, which improves the surface charge density and anti-fouling ability.

Benefits of technology

It realizes a high net friction charge density for long-term storage of surfaces, improves the output performance of friction nanogenerators, and is suitable for self-powered body motion sensing and water wave energy collection, with excellent friction electrical performance and commercial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686028A_ABST
    Figure CN119686028A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano-generators, in particular to a triboelectric material of nano-porous composite fibers and a preparation method and application of the triboelectric material of the nano-porous composite fibers, and the preparation method comprises the following steps: adding polyvinylidene fluoride and perfluoroethylene propylene copolymer nanoparticles into a mixed solvent of N, N-dimethylacetamide / acetone; uniformly mixing to obtain a polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion; and carrying out electrostatic spinning on the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion to obtain the triboelectric material. The triboelectric material prepared through the method is a high-charge-density super-hydrophobic nano-generator material based on electrostatic spinning, the electrostatic spinning porous composite fiber material is used as a friction medium layer, high surface charge, hydrophobicity and fouling resistance are achieved, and the performance of a flexible solid-liquid interface nano-generator is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanogenerators, and in particular to a triboelectric material of nanoporous composite fibers and a preparation method and application thereof. Background Art

[0002] The triboelectric nanogenerator is a new type of power generation technology based on contact electrification and electrostatic induction. It directly converts the tiny, low-frequency, and difficult-to-use distributed mechanical energy in the environment into electrical energy. It has many advantages such as small size, light weight, low price, diverse structure, and strong adaptability, which has attracted widespread attention from researchers at home and abroad. The increasing shortage of fossil energy and the continuous growth of energy demand have promoted the rapid development of advanced technologies that match energy collection and storage. In order to achieve social sustainability, eco-friendliness, and prosperity, the trend of shifting from fossil fuels to clean and renewable energy is unstoppable. The triboelectric nanogenerator (TENG) developed by Wang Zhonglin's team that converts mechanical energy into electrical energy is one of the best choices for this energy in the new era. This is a revolutionary technology that has unparalleled superiority in obtaining various forms of mechanical energy in a low-frequency environment and is likely to make a significant contribution to the sustainable development of global energy.

[0003] However, the development of blue energy of friction nanogenerators faces challenges of durability and corrosion resistance. Research on wave energy generation and application of friction nanogenerators at solid-liquid interfaces. The solid / liquid interface friction nanogenerator based on a planar structure ingeniously uses waves as a movable component, without the need for additional energy capture and transmission components. It has a flexible multilayer membrane structure, flexible and rollable cutting, portable and flexible, and realizes a wave generator device with high power generation energy density, promoting the blue energy of friction nanogenerators. One of the core parts of the development and utilization of blue energy of solid-liquid friction nanogenerators is the long-term storage problem of high friction charge density of surface materials. Its electrification performance, charge storage capacity, surface anti-fouling and other capabilities determine the output performance of friction nanogenerators. Traditional blue energy friction medium materials are mainly organic polymer films, which have the characteristics of high flexibility, high dielectric strength, and strong ability to lose / gain electrons. However, the shortcomings of polymer materials such as poor air permeability, easy contamination, and difficult processing have caused certain obstacles to the development and utilization of blue energy of friction nanogenerators. Compared with existing polymer film materials, the porous composite fiber membrane based on electrospinning has the characteristics of high flux, large relative area, and scalable preparation, which is a good complement to the polymer film and shows its application potential in high output, wearable, weather resistance, and self-cleaning. The surface charge density of triboelectric materials is less than 200μC m -2, which is much lower than that of polymer materials under the same conditions. The low charge density limits the application development in the field of friction nanopower generation. Therefore, how to improve the surface charge density of spinning membrane materials through structural optimization of surface friction power-saving materials and material system design to achieve long-term high power output based on friction nanogenerators. In addition, portable wearable electronic devices have the ability to be integrated into clothes or worn as accessories, which not only replaces traditional large electronic devices in terms of function but also improves the quality of life. However, wearable sensors usually have high energy consumption and require a stable power supply to maintain their operation. Traditional batteries need to be charged frequently, and their unique rigidity also affects the flexibility and lightweight of the manufactured wearable devices. Summary of the invention

[0004] Based on this, the present invention proposes a one-step high-performance super-hydrophobic nanoporous composite fiber triboelectric material and a preparation method and application thereof.

[0005] According to a first aspect of the present invention, there is provided a method for preparing a triboelectric material of a nanoporous composite fiber, comprising the following steps:

[0006] Adding polyvinylidene fluoride and perfluoroethylene propylene copolymer nanoparticles into a mixed solvent of N,N-dimethylacetamide / acetone, and mixing them evenly to obtain a polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion;

[0007] The triboelectric material is obtained by electrostatically spinning the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion.

[0008] According to an embodiment of the present invention, the perfluoroethylene propylene copolymer nanoparticles account for 0-65wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion;

[0009] The polyvinylidene fluoride accounts for 35-100wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion.

[0010] According to an embodiment of the present invention, the particle diameter of the perfluoroethylene propylene copolymer nanoparticles ranges from 100 nm to 100 μm;

[0011] The average molecular weight of the polyvinylidene fluoride is in the range of 100,000 to 1.8 million.

[0012] According to an embodiment of the present invention, adding perfluoroethylene propylene copolymer nanoparticles into a mixed solvent of N,N-dimethylacetamide / acetone comprises:

[0013] Perfluoroethylene propylene copolymer nanoparticles are added to a mixed solvent of N,N-dimethylacetamide / acetone, and magnetic stirring is performed for 1-10 hours.

[0014] According to an embodiment of the present invention, adding polyvinylidene fluoride into a mixed solvent of N,N-dimethylacetamide / acetone comprises:

[0015] Add polyvinylidene fluoride to the N,N-dimethylacetamide / acetone mixed solvent, heat and stir with magnetic stirring, the stirring time is 1-10 hours, and the heating temperature is 40-80°C.

[0016] According to an embodiment of the present invention, the parameters of the electrospinning are set as follows: the spinning voltage is 5-25 kV, and the roller receiving distance is 15-25 cm.

[0017] According to a second aspect of the present invention, there is provided a triboelectric material of nanoporous composite fibers obtained by the above-mentioned preparation method.

[0018] According to a third aspect of the present invention, a friction nanogenerator using the triboelectric material of the nanoporous composite fiber is provided.

[0019] According to an embodiment of the present invention, a negative friction layer is included, which is obtained by cutting the above-mentioned triboelectric material and pasting it on the surface of a conductive material.

[0020] According to an embodiment of the present invention, the thickness of the negative friction layer is in the range of 0.005-0.40 mm.

[0021] According to a fourth aspect of the present invention, there is provided an application of the above-mentioned triboelectric material of nanoporous composite fibers in a motion sensing device or solid-liquid contact power generation based on friction electrification.

[0022] It can be seen from the above technical solutions that the triboelectric material of nanoporous composite fibers provided by the present invention and its preparation method and application have the following beneficial effects:

[0023] The present invention provides a one-step high-performance super-hydrophobic nanoporous composite fiber triboelectric material, which realizes the requirement of long-term storage of high net triboelectric charge density on the surface. By designing a polyvinylidene fluoride / ethylene propylene fluoride nanoparticle porous nanofiber membrane with air permeability, waterproofness, surface super-hydrophobicity and high specific surface area, a high-density net triboelectric charge is achieved, thereby realizing a high-electric output triboelectric nanogenerator for self-powered body motion sensing and water wave energy harvesting.

[0024] The friction nanoengine prepared by the friction electric material provided by the present invention has a maximum short-circuit voltage of 372μA, an open-circuit voltage of 1264V, and a transfer charge density of 294μC / m 2, 42.2% higher than the transferred charge density of polytetrafluoroethylene film. After 141,860 working cycles, the triboelectric material still maintains the best performance with almost no attenuation. Based on its excellent triboelectric properties, the triboelectric material has excellent performance in self-powered body motion sensing and mechanical energy harvesting, and can be used for continuous self-powered monitoring of offshore environments. Our triboelectric material has high triboelectric performance, surface superhydrophobicity and breathability, does not require additional surface modification, simplifies the one-step molding process, has higher profits than the conversion method, and is feasible for commercial applications.

[0025] The triboelectric material provided by the present invention is a high charge density super hydrophobic nanogenerator material design based on electrospinning. By using the electrospinning porous composite fiber material as the friction medium layer, high surface charge and hydrophobic anti-fouling are achieved, thereby improving the performance of the flexible solid-liquid interface nanogenerator. The electrospinning porous composite fiber material can be used not only for flexible solid-liquid interface nanogenerators, but also for applications such as electronic skin sensing based on triboelectric charging, which are commonly used at this stage. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of an electrospinning device for triboelectric materials in an embodiment of the present invention;

[0027] Figure 2 is a structural representation diagram of the triboelectric material in an embodiment of the present invention; wherein, Figure 2 a is the SEM image of the triboelectric material at 20 μm scale; Figure 2 b is the SEM image of the triboelectric material at 1 μm scale; Figure 2 c is the AFM surface morphology image of the triboelectric material at 10 μm scale; Figure 2 d is the SEM phase image of the triboelectric material at 800 nm scale; Figure 2 e AFM surface morphology; Figure 2 f is the friction charge phase diagram of the EFM surface;

[0028] Figure 3 Schematic diagram of the working modes of four kinds of friction nanogenerators in the embodiments of the present invention;

[0029] Figure 4 A test schematic diagram and an electrical output characteristic diagram of a friction nanogenerator according to an embodiment of the present invention; Figure 4 a is the schematic diagram of PFPN-TENG; Figure 4 b is the graph showing the change of the electrical output short-circuit current with the number of impact cycles; Figure 4 c is the short-circuit current and the amount of transferred charge;

[0030] Figure 5The effects of different excitation frequencies or connecting different resistors on the PFPN-TENG in the embodiment of the present invention; Figure 5 a is the output current of the PFPN-TENG nanogenerator with different excitation frequencies; Figure 5 b is a schematic diagram of the output power of the PFPN-TENG connected to different resistors in an embodiment of the present invention;

[0031] Figure 6 The TENG power generation output is compared between the PFPN film and other friction materials in the embodiment of the present invention;

[0032] Figure 7 The fiber structure SEM images of four typical fiber membranes in the comparative examples of the present invention; Figure 7 a SEM image of pure PVDF solid fiber membrane; Figure 7 b SEM image of pure PVDF porous fiber membrane; Figure 7 c is the SEM image of PVDF / FEP NPs composite solid fiber membrane; Figure 7 d SEM image of PVDF / FEP NPs porous fiber membrane with FEP NPs and nanopores inside PVDF fibers;

[0033] Figure 8 This is the influence diagram of the ratio and thickness of FEP NPs in the superhydrophobic PFPN composite porous fiber membrane; Figure 8 a is the effect of FEPNPs content; Figure 8 b is the output current and the amount of transferred charge at different thicknesses;

[0034] Fig. 9 Schematic diagram of the application of the all-fiber air-permeable motion sensor PFPN-TENG assembled with super-hydrophobic PFPN composite porous nanofiber membrane in the embodiment of the present invention; Fig. 9 a is a schematic diagram of the structure of superhydrophobic PVDF / FEP NPs composite porous nanofiber membrane; Fig. 9 b is a schematic diagram of the structure of the all-fiber air-permeable motion sensing TENG assembled from super-hydrophobic PVDF / FEP NPs composite porous nanofiber membrane;

[0035] Fig.10 This is the output signal result of the full-fiber air permeable motion sensor PFPN-TENG in an embodiment of the present invention. Fig.10 a The device is fixed on the finger and outputs a voltage signal through the finger movement in the air; Fig.10 b is the voltage signal output of the all-fiber breathable motion sensing PFPN-TENG device fixed on the finger and moving through the finger underwater; Fig.10 c is the voltage output signal of the full-fiber breathable motion sensor when struck; Fig.10 d is the voltage output signal of the full-fiber air permeability motion sensor when folded;

[0036] Fig.11 Schematic diagram of preparing a flexible solid-liquid contact PFPN-TENG in an independent layer mode in an embodiment of the present invention;

[0037] Fig.12 This is an application demonstration of the flexible solid-liquid contact PFPN-TENG assembled from a super-hydrophobic PFPN composite porous nanofiber membrane in an embodiment of the present invention; Fig.12 a is a schematic diagram of the flexible PFPN-TENG wave energy power generation application device; Fig.12 b Photo of flexible PFPN-TENG device; Fig.12 c Current output of flexible PFPN-TENG wave power generation; Fig.12 d is the output current peak and voltage peak of the flexible wave PFPN-TENG of PVDF / FEP NPs connected with different resistances in the embodiment of the present invention; Fig.12 e Output power peaks of flexible PFPN-TENG wave power generation connected with different resistances; Fig.12 f Schematic diagram of charging different capacitors by flexible PFPN-TENG wave power generation.

[0038] In the figure: 1-FEP NPs dispersion, 2-PVDF / FEP NP spinning emulsion, 3-electrospinning device, 4-fiber structure, 5-fiber membrane structure. DETAILED DESCRIPTION

[0039] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0040] According to a first aspect of the present invention, there is provided a method for preparing a triboelectric material of a nanoporous composite fiber, comprising the following steps:

[0041] Adding polyvinylidene fluoride (PVDF) and perfluoroethylene propylene copolymer nanoparticles (FEP NPs) into a mixed solvent of N,N-dimethylacetamide / acetone, and mixing them evenly to obtain a polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion);

[0042] The polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion) was electrospun to obtain a triboelectric material (PFPN film).

[0043] The high friction negative charge layer is prepared by the dual strategy of perfluoroethylene propylene copolymer nanoparticles (FEP NPs) and porous nanofibers. The one-step forming method is used for the preparation, without further material treatment and modification. The nanofibers of the triboelectric material (PFPN film) are distributed in irregular beads on the porous nanofibers to form a multi-scale micro-nano structure. The outermost layer of the nanofibers is perfluoroethylene propylene copolymer nanoparticles (FEP NPs) with low surface energy, which has excellent surface superhydrophobicity and a water contact angle of 152°.

[0044] Perfluoroethylene propylene copolymer nanoparticles (FEP NPs) and nanopores are uniformly embedded in the three-dimensional hierarchical micro-nanostructure porous nanofiber framework. The triboelectric material (PFPN film) has an ultra-high specific surface area. Compared with general polymer film materials, its composite nanoporous fiber structure changes the triboelectric charge storage from two-dimensional surface storage to three-dimensional storage, effectively increasing the net triboelectric charge density.

[0045] At the same time, the doping of perfluoroethylene propylene copolymer nanoparticles (FEP NPs) makes the triboelectric material (PFPN film) have extremely high tribo-negative polarity, thereby providing a higher triboelectric charge capture capability and significantly increasing the net surface charge density. In particular, the good surface super-hydrophobicity improves the separation of the double-layer triboelectric charge at the solid-liquid interface, thereby reducing the surface triboelectric charge loss, increasing the net surface triboelectric charge density, and significantly improving the anti-environmental interference capability of the friction material, making great progress in the flexible solid-liquid interface triboelectric nanogenerator (TENG).

[0046] After more than 141,860 working cycles, the triboelectric charge density of the prepared triboelectric material (PFPN film) reached 294 μCm -2 , which is 142.2% of that of commercial polytetrafluoroethylene film, and has good self-powered body motion sensing and human motion energy harvesting performance. The solid-liquid contact friction nanogenerator (PFPN-SLTENG) based on flexible triboelectric material (PFPN film) achieves high electrical output by harvesting water wave energy, with an average volume power density of 544.1 Wm -3 , has great potential in continuous self-powered monitoring of offshore environments.

[0047] According to an embodiment of the present invention, the perfluoroethylene propylene copolymer nanoparticles (FEP NPs) account for 0-65wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion);

[0048] The polyvinylidene fluoride (PVDF) accounts for 35-100wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion).

[0049] According to an embodiment of the present invention, the particle diameter of the perfluoroethylene propylene copolymer nanoparticles (FEP NPs) ranges from 100 nm to 100 μm;

[0050] The average molecular weight of polyvinylidene fluoride (PVDF) ranges from 100,000 to 1.8 million.

[0051] According to an embodiment of the present invention, perfluoroethylene propylene copolymer nanoparticles (FEP NPs) are added to a mixed solvent of N,N-dimethylacetamide / acetone, comprising:

[0052] Perfluoroethylene propylene copolymer nanoparticles (FEPNPs) were added to a mixed solvent of N,N-dimethylacetamide / acetone and magnetically stirred for 1-10 hours.

[0053] According to an embodiment of the present invention, polyvinylidene fluoride (PVDF) is added to a mixed solvent of N,N-dimethylacetamide / acetone, comprising:

[0054] Add polyvinylidene fluoride (PVDF) to a N,N-dimethylacetamide / acetone mixed solvent, heat and stir with magnetic force, the stirring time is 1-10 hours, and the heating temperature is 40-80°C.

[0055] According to an embodiment of the present invention, the mixed solution may be added with a solvent simultaneously or in steps, and the heating method may be a water bath or an oil bath.

[0056] According to an embodiment of the present invention, the preparation method may further include:

[0057] Adding perfluoroethylene propylene copolymer nanoparticles (FEPNPs) into a mixed solvent of N,N-dimethylacetamide / acetone and stirring by magnetic force to obtain a FEP NPs-N,N-dimethylacetamide / acetone dispersion;

[0058] Adding polyvinylidene fluoride (PVDF) to a FEP NPs-N,N-dimethylacetamide / acetone mixed solvent, heating in a water bath and magnetic stirring, to obtain a polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion);

[0059] The polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion (PVDF / FEP NPs spinning emulsion) was electrospun to obtain a triboelectric material (PFPN film).

[0060] According to an embodiment of the present invention, the parameters of electrospinning are set as follows: spinning voltage 5-25 kV, roller receiving distance 15-25 cm.

[0061] According to a second aspect of the present invention, a triboelectric material (PFPN film) of nanoporous composite fibers obtained by the above-mentioned preparation method is provided.

[0062] The present invention provides a triboelectric material (PFPN film) that improves the electrical output performance of the nanogenerator by improving the dielectric properties of the nanofibers. FEP and PTFE contain fluorine, which is the element with the highest electronegativity, and have a strong ability to obtain electrons, but FEP and PTFE are difficult to process. PVDF also contains more electronegative fluorine elements and can be easily dissolved and processed. Electrospun nanofibers have a high specific surface area and porosity, providing sites for the negative friction layer to generate friction charges; at the same time, they have good air permeability and stretchability, and are more suitable for wearable devices on the human body than traditional batteries with inherent rigidity.

[0063] The triboelectric material (PFPN membrane) with nanofiber structure can significantly improve the electrical output performance of the triboelectric nanogenerator (TENG). The microsphere structure, nanopores and polyperfluoroethylene propylene (FEP) in the superhydrophobic PVDF / FEP composite porous nanofiber membrane can improve the surface roughness and surface friction polarity of the friction pad layer, thereby increasing the surface friction charge density of the friction material and enhancing the output electrical signal and mechanical energy capture conversion of the triboelectric nanogenerator (TENG).

[0064] In addition, the microsphere beaded PVDF / FEP composite porous nanofibers have a super-hydrophobic effect due to the embedded polyperfluoroethylene propylene (FEP) nanoparticles with more CF bonds and the fiber micron beaded structure forming a surface lotus effect, which can significantly improve the performance of the friction nanogenerator (TENG) in a high humidity environment. The super-hydrophobic PVDF / FEP composite porous nanofiber membrane can not only be used for flexible solid-liquid interface nanogenerators, but also can be used for applications such as electronic skin sensing based on triboelectric charging, which is commonly used at this stage.

[0065] Compared with the prior art, the super-hydrophobic triboelectric material (PFPN film) of the present invention is a promising friction nanogenerator (TENG) friction layer material, especially its application field in the friction nanogenerator (TENG). It is mainly through the doping of dielectric materials such as nanoparticles of polyperfluoroethylene propylene (FEP) or polytetrafluoroethylene (PTFE), and the control of electrospinning conditions and other methods to achieve a one-step surface super-hydrophobic micro-nanostructure high friction polarity high net charge density porous fiber. The method is simple, no subsequent material modification is required, and it is suitable for industrial production. The obtained super-hydrophobic micro-nanostructure triboelectric material (PFPN film) has uniform composition, high porosity, good air permeability, good waterproofness, good surface super-hydrophobic properties and excellent triboelectric performance.

[0066] The present invention provides a method with simple process, low cost and large-scale production for preparing a super-hydrophobic micro-nanostructured high-friction polarity and high net charge density porous fiber film for triboelectric material (PFPN film), which has high friction performance and a wide range of applications.

[0067] According to an embodiment of the present invention, the triboelectric material (PFPN membrane) is a super-hydrophobic composite porous fiber membrane, and the polyperfluoroethylene propylene (FEP) nanoparticles on the surface of the super-hydrophobic composite porous fiber are semi-embedded in the fiber, and more -CF3 and -CF2 groups are on the fiber surface.

[0068] According to an embodiment of the present invention, the diameter of the super-hydrophobic composite porous fiber is 0.7-3 μm.

[0069] According to an embodiment of the present invention, the diameter of the nanoscale protrusions on the surface of the super-hydrophobic composite porous fiber is 100 nm-250 nm.

[0070] According to an embodiment of the present invention, the diameter of the nanopores of the super-hydrophobic composite porous fiber is 10-400 nm.

[0071] According to an embodiment of the present invention, polyvinylidene fluoride (PVDF) in the triboelectric material (PFPN film) has a higher β-phase crystal.

[0072] According to an embodiment of the present invention, the particle size of the micron spherical beads formed by the super-hydrophobic composite porous fibers is 2-5 μm.

[0073] According to an embodiment of the present invention, the surface contact angle of the triboelectric material (PFPN film) is 152±2°.

[0074] According to the embodiments of the present invention, the BET specific surface area of ​​the triboelectric material (PFPN film) can reach .

[0075] According to a third aspect of the present invention, a friction nanogenerator (PFPN-TENG) using the triboelectric material (PFPN film) of the nanoporous composite fiber is provided.

[0076] The four basic working modes of the friction nanogenerator (PFPN-TENG) include vertical contact-separation mode, horizontal sliding mode, single electrode mode and independent layer mode. Based on the triboelectric material (PFPN film) as the negative electric friction layer (friction layer 1), the working mode of the friction nanogenerator is selected according to the application environment, and the friction nanogenerator (PFPN-TENG) with the corresponding structure is prepared. Figure 3 Various modes of friction nanogenerators (PFPN-TENG) prepared based on triboelectric materials (PFPN films) are listed. In the vertical contact-separation mode, two dielectric films of different materials are stacked face to face and form surface charges of opposite signs when in contact. When these surfaces are separated due to external forces, an induced potential difference is formed between the two electrodes, driving electrons to flow between the two electrodes. The horizontal sliding mode is similar to the vertical contact-separation mode, but relative slip occurs between the two dielectric films along the horizontal direction parallel to the surface. This sliding can generate friction charges on the two surfaces, forming polarization, and driving electrons to flow between the upper and lower electrodes. The single electrode mode is that the friction nanogenerator (PFPN-TENG) has only one electrode, and the charge generated by friction can be directly accumulated on the electrode to form a potential difference. This mode is suitable for occasions where a simplified structure is required. The independent layer mode is that the friction layer and the electrode layer are independent, and the charge generated by friction can be transferred between the independent layers to form a potential difference. This mode is suitable for occasions where high flexibility and independent power sources are required. The vertical contact-separation mode is suitable for collecting tiny mechanical energy generated by biological movements, such as heart beating, breathing, etc. The horizontal sliding mode is suitable for occasions that require periodic sliding, such as clothing friction. The single electrode mode is suitable for occasions that simplify the structure. The independent layer mode is suitable for occasions that require high flexibility and independent power supply.

[0077] Taking the friction nanogenerator (PFPN-TENG) in contact-separation mode as an example, the two friction layers of the friction nanogenerator (PFPN-TENG) periodically contact and separate, and the high friction negative polarity perfluoroethylene propylene copolymer nanoparticles (FEP NPs) in the surface fibers of the triboelectric material (PFPN film) obtain electrons due to the contact electrification effect, so that the surface fibers capture a large number of friction electrons and have a high negative potential. In the subsequent contact-separation process, friction movement occurs between the surface and the internal superhydrophobic composite porous fibers, and the friction electrons are transferred from the surface layer fibers to the internal fibers, so that the surface friction electrons decrease and the inner layer fiber friction electrons increase. At the same time, the surface nanofibers continue to capture electrons from the friction positive layer until the friction negative electrons in the entire triboelectric material (PFPN film) finally reach the triboelectric material (PFPN film) triboelectric electron storage site to capture all the friction electrons to reach saturation. In this way, the friction charge storage of the friction layer changes from two-dimensional surface storage to three-dimensional storage, effectively increasing the net friction charge density. The process of friction electrons transferring from the outer layer to the inner layer of the triboelectric material (PFPN film) and the process of the outer fiber of the triboelectric material (PFPN film) snatching friction electrons from the positive friction layer occur simultaneously, until the entire triboelectric material (PFPN film) is filled with friction electrons and saturated, and the inner and outer fibers have the same saturated friction potential, thus obtaining an ultra-high friction charge density.

[0078] like Figure 3 As shown, the contact-separation mode friction nanogenerator (PFPN-TENG) based on triboelectric material (PFPN film) includes a first triboelectric layer 1 and a second triboelectric layer 2, wherein the first triboelectric layer 1 is a triboelectric material (PFPN film). The triboelectric material (PFPN film) is prepared by electrospinning. The first triboelectric layer 1 is spun on an aluminum foil tape by electrospinning.

[0079] The triboelectric layer 2 is the positive triboelectric layer of the friction nanogenerator (PFPN-TENG), and a variety of triboelectric materials can be selected, such as polymer films, electrospun fiber membranes of corresponding materials, and conductive spun fiber membranes. Materials with strong electron loss ability and large specific surface area are preferred to further improve the electrical output performance of the friction nanogenerator (PFPN-TENG). Here, the triboelectric layer 2 is a transparent polyethylene terephthalate film with a thickness of 30 μm.

[0080] It is pointed out that the problems of low surface charge density and easy surface fouling of spinning membrane materials can be solved by material selection and preparation parameter optimization, laying the foundation for high-power output and anti-fouling friction nanogenerators.

[0081] By designing the material system, the type of doped materials, the crystal orientation and the preparation process, the surface morphology is controlled, thereby controlling the surface porosity, surface super-hydrophobicity and other properties;

[0082] High charge density superhydrophobic electrospun materials can be applied to a variety of basic triboelectric nanogenerators (PFPN-TENG).

[0083] Applying superhydrophobic micro-nanostructured triboelectric materials (PFPN films) to friction nanogenerators (PFPN-TENGs) can improve the microcapacitor structure of the material, increase the net friction charge density and thus improve the output performance of the nanogenerator. It can be used in self-powered wearable sensors and friction nanogenerator devices to collect and convert mechanical energy in the environment, providing a new preparation method and idea for realizing high-performance friction nanogenerators (PFPN-TENGs).

[0084] The present invention prepares an electrospun friction nano-electric material of super-hydrophobic micro-nanostructure composite porous fiber as the negative electric friction layer of the friction nanogenerator (PFPN-TENG). The nanofibers with porous structure and multi-scale micro-nanostructure can effectively increase the contact area of ​​the friction layer, and the content of polyperfluoroethylene propylene nanoparticles added in the negative friction layer can effectively improve the triboelectric output performance.

[0085] According to an embodiment of the present invention, a negative friction layer is included, which is obtained by cutting a friction nanogenerator (PFPN-TENG) and then pasting it on the surface of a conductive material.

[0086] According to an embodiment of the present invention, the thickness of the negative friction layer is in the range of 0.005-0.40 mm.

[0087] According to a fourth aspect of the present invention, there is provided an application of a triboelectric material (PFPN film) in an electronic skin sensor device or solid-liquid contact power generation based on triboelectric charging.

[0088] Preparation of breathable all-fiber friction nanogenerator (PFPN-TENG) device: TPU particles (Elastollan, 1180A) were added to hexafluoroisopropanol (HFIP, Aladdin) solvent at a concentration of 4wt%. Then stirred at room temperature for about 6h. Silver nanowires (AgNWs) were dispersed in alcohol with a concentration of 1mg / mL. TPU nanofibers and silver nanowires (AgNWs) were collected simultaneously on aluminum foil covered on a rotating drum. The applied electrospinning and electrostatic spraying positive electrode voltage was about 15kV, and the negative electrode voltage was about 2kV. The injection rates of TPU solution and AgNW solution were 0.2mLmin, respectively. -1 and 1.3 mL min -1. Pre-spin TPU (waterproof insulating TPU layer) for 1h, TPU spinning and silver nanowires (AgNWs) spraying for 4h, and prepare conductive AgNW / TPU electrodes after vacuum drying at 60℃ for 4h. In the second step, prepare the conductive layer on aluminum foil, and cut the conductive layer (24mm×24mm) with a laser cutter after drying. After connecting the output line with conductive silver glue (SPI Supplies), re-fix it on aluminum foil for electrostatic spinning of triboelectric material (PFPN film). After drying at 80℃ for 4h, the negative contact layer with integrated air-permeable conductive fiber friction layer is prepared. The bracket between the positive and negative triboelectric layers is a rectangular VHB double-sided tape (3M4910) (30mm×30mm×2mm, hollow 24mm×24mm). In the third step, assemble: connect the wires to the two conductive AgNW / TPU electrodes with SPI silver glue. Paste the conductive AgNW / TPU layer and the negative friction layer on both sides of the VHB gap to form a sandwich structure. Finally, the edges of the full-fiber breathable triboelectric nanogenerator (PFPN-TENG) were waterproofed using polydimethylsiloxane (PDMS).

[0089] The friction nanogenerator (PFPN-TENG) made of a full-fiber breathable multi-layer film is used to collect the mechanical energy of human activities. In the future, self-powered human motion monitoring can be realized. The friction nanogenerator (PFPN-TENG) can be integrated into a swimsuit, which can simultaneously realize the collection of mechanical energy of human motion into electrical energy and self-powered motion sensing.

[0090] The prepared all-fiber breathable triboelectric nanogenerator (PFPN-TENG) consists of three layers, two conductive AgNW / TPU composite nanofiber layers and triboelectric material (PFPN film), in which the middle triboelectric material (PFPN film) and the upper composite conductive layer are made in one piece, forming the negative friction contact part. The conductive composite layer below is the negative friction layer, which plays two roles: negative friction material and electrode.

[0091] In addition, the excellent surface superhydrophobicity and high negative triboelectric properties make the PFPN film a very promising solid-liquid contact triboelectric nanogenerator (PFPN-TENG), which is expected to realize self-powered real-time marine environment monitoring equipment such as temperature sensors, light intensity sensors, water quality and other hydrological monitoring by collecting water wave energy. The flexible film solid-liquid contact triboelectric nanogenerator (PFPN-TENG) device can be placed in the most severely corroded marine steel structures such as offshore structures or pipeline splash zones, ship ballast tanks, etc., to achieve high power output and surface protection.

[0092] like Fig.11As shown in the figure, a flexible solid-liquid contact triboelectric nanogenerator (PFPN-TENG) with independent layer mode is prepared, and the steps include: first, a PET substrate film with a size of 140mm×110mm×100μm is cut out by laser cutting technology. A PET electrode mask (110mm×110mm×50μm) is prepared by laser cutting technology, including a working electrode and a positive electrode and a negative electrode. The working electrode (total size is 110mm×82mm) consists of 15 rectangular arrays, each rectangular working electrode is 110mm, 5mm wide, and the spacing between adjacent rows is 0.5mm. Then the electrode mask is pasted on a completely cleaned substrate, and a group of conductive aluminum electrodes with a thickness of 200nm are prepared by magnetron sputtering. The rectifier chip is connected to the two ends of the electrode unit. The two ends of the generating electrode are respectively connected to the opposite pins of the patch rectifier diode, and the outermost end is connected to the remaining pins of the positive and negative parent electrodes. Two enameled wires are connected to the positive and negative electrodes respectively. Rinse and clean with acetone, isopropanol and alcohol. Finally, the substrate with electrodes was fixed on the electrospinning receiving roller, and the triboelectric material (PFPN film) was prepared on it by using the electrospinning device. After vacuum drying at 80°C for 4 h, a flexible solid-liquid contact triboelectric nanogenerator (PFPN-TENG) was obtained.

[0093] The technical solution of the present invention is described in detail below through preferred embodiments. It should be noted that the specific embodiments below are only used for illustration and are not used to limit the present invention.

[0094] like Figure 1 As shown, the electrospinning equipment used in this embodiment includes: a liquid storage device (syringe), a roller and a high-voltage power supply. The liquid storage device is connected to the liquid supply and pushing device, and the roller serves as a receiving device. The positive electrode of the high-voltage power supply is connected to the liquid storage device, and the negative electrode is connected to the roller. An electric field of a certain intensity is formed between the positive electrode and the negative electrode, so that the surface of the spinning liquid on the surface of the liquid storage device forms fluctuations, similar to the shape of a Taylor cone, and is further stretched into nanofibers.

[0095] Embodiment 1:

[0096] Preparation of triboelectric materials: 12wt% FEP NPs powder was added to a mixed solvent of N,N-dimethylacetamide (DMAC) and acetone (AC) (volume ratio 18:7), and fully dispersed under magnetic stirring at room temperature for 4h to form a FEP NPs dispersion with a concentration of 1.6wt% PVDF powder was added to the FEP NPs dispersion, heated and stirred at 60℃ for 4h, and PVDF was fully dissolved to form a PVDF / FEP NPs spinning emulsion; the PVDF / FEP NPs spinning emulsion was transferred to a 5mL syringe and placed on a push pump, and a syringe needle with an inner diameter of 0.33mm was used for spinning. The aluminum foil tape wrapped on the drum was used as a receiving device and can be directly used as the electrode of TENG. After connecting the electrodes of the high-voltage power supply to the syringe needle and the drum respectively, the spinning was carried out at a voltage of 8kV and -0.5kV, a feed rate of 1.8mL / h, and a receiving distance of 20cm. The electrospinning temperature was 24±3℃ and the humidity was 35±5%. The collected fiber membrane can be dried at room temperature or placed in an oven at 80°C for 4 hours to remove the influence of residual solvent. The electrospinning technology is used for one-step molding without further modification to obtain a super-hydrophobic PFPN membrane with a hierarchical micro-nano porous nanofiber structure. Preferably, the thickness of the PFPN membrane is 40±3 μm.

[0097] Structural characterization

[0098] like Figure 2 As shown in the figure, the nanocomposite porous fibers in the PFPN membrane contain microsphere beads, which realizes the PFPN composite porous nanofiber membrane with multi-scale micro-nano structure, nanopores and embedded distribution of FEP NPs. The PFPN nanofibers are distributed with irregular micron beads with a diameter of 2-5μm on the porous nanofibers with a diameter of 700-3000nm, and FEPNPs and nanopores are evenly distributed in the nanofibers. The outermost layer of the porous PFPN nanofibers is FEPNPs nano-scale protrusions and nano-pits, forming a multi-scale micro-nano beaded structure. The FEPNPs embedded in the nanofibers contain fluorine elements with the highest electronegativity and have strong electron-accepting ability. The setting of the PFPN membrane can improve the electrical output performance of TENG. The contact angle of the obtained material was tested by a contact angle meter, and the contact angle was 152±2°, indicating that the PFPN membrane has good superhydrophobicity. The microsphere beads of the PFPN membrane can improve the surface roughness and hydrophobicity of the friction layer, thereby improving the applicability of the friction layer in various environments. This good surface superhydrophobicity promotes the separation of the friction charge double layer at the solid-liquid interface, thereby reducing the surface friction charge loss and increasing the net surface friction charge density. The PFPN membrane has a high specific surface area and porosity. The BET specific surface area of ​​the PFPN membrane calculated from the nitrogen adsorption-desorption isotherm is 10.785 m 2 g -1The pore size distribution diagram further confirmed that the pore size of the PFPN membrane ranges from 10 to 400 nm, concentrated in the mesopores and macropores. FEPNPs have low surface energy and high triboelectric negative polarity, and their distribution plays a decisive role in improving the triboelectric properties of the PFPN membrane, providing sites for the triboelectric layer to generate triboelectric charges, providing higher triboelectric charge capture capabilities, and greatly improving the net surface charge density.

[0099] The PFPN membrane is based on integrated electrospinning technology, does not require surface modification, has a simple preparation process, and has good air permeability and stretchability. Compared with traditional film materials with inherent rigidity, it is suitable for wearable devices. In addition, the composite porous nanofibers of the PFPN membrane have a hydrophobic effect due to the low surface energy characteristics of the FEP and PVDF materials themselves and the lotus effect of the multi-scale microsphere beaded fiber structure, which can be used as a method to deal with TENG applications in high humidity environments.

[0100] The morphology and surface triboelectric capability of the samples were observed using an atomic force microscope (MFP-3D Origin Atomic Force Microscope). Figure 2 c and Figure 2 As shown in d.

[0101] Generally speaking, in MFP-3D systems, electrostatic attraction (negative charge) leads to an increase in phase, resulting in brighter colors; conversely, repulsion (positive charge) leads to a decrease in phase, resulting in darker colors. For example, the AFM morphology and EFM phase diagram of the PFPN film, Figure 2 c and Figure 2 As shown in Figure d, there are concentrated positive phase shift regions in the potential of the PFPN composite nanoporous fiber. The reason for these high displacements is the electrical displacement generated by the probe when scanning the new morphology of the surface. Combined with the structure of the PFPN membrane ( Figure 2 c), the area with the highest degree of spontaneous polarization of the unit cell is exactly the area where FEPNPs exist. This shows that the addition of FEPNPs significantly improves the electron capture ability of PFPN, significantly improves the negative triboelectric properties of PFPN, and helps to improve the triboelectric output performance. What is more worth mentioning is that the electric displacement intensity of the topmost fibers does not seem to be much different from that of the inner fibers. Therefore, we can speculate that the triboelectrons that are forcibly captured during the contact-separation process are transferred from the outer fibers to the inner fibers through the relative movement between the nanofibers.

[0102] The PFPN membrane prepared in Example 1 was used to assemble the contact-separation mode PFPN-TENG.

[0103] like Figure 3As shown, the aluminum tape with PFPN film and the transparent polyethylene terephthalate film (thickness 40) with aluminum foil 4 on one side were cut into 5×5 cm 2 The size of the conductive enameled wire is then connected to the aluminum foils 3 and 4 respectively with conductive silver glue, and the aluminum foil is adhered to the transparent acrylic glass plate of polymethyl methacrylate as the substrate using insulating double-sided polyimide tape to form a contact-separation mode PFPN-TENG. Finally, the two parts of the PFPN-TENG are fixed on the linear motor respectively, and the PFPN film and the PET film are placed relative to each other so that they can move in contact and separation in the linear motor (Linmot), so that the two friction layers are fully in contact when under pressure and completely separated when separated (such as Figure 4 a) Connect the wire to the test electrometer and do an electrical output test.

[0104] The PFPN-TENG is connected to the electrostatic tester through a wire, and the linear motor moves periodically at a frequency of 0.82Hz, with a separation distance of 50mm and a contact force of 28N. The PFPN-TENG has an electrical output short-circuit current of 372μA ( Figure 4 b), and after 141860 impact cycles, there was no attenuation, and the charge was 0.735μC ( Figure 4 c).

[0105] The frequency response characteristics of the PFPN film were measured. Figure 5 As shown in Figure a, when the operating frequency increases from 0.82 Hz to 5 Hz, the short-circuit current peak of PFPN-TENG does not change much, which indicates that the negative charge in the composite PFPN layer is highly stable, and the surface friction charge is not easily lost after reaching saturation, ensuring that PFPN-TENG works efficiently and stably.

[0106] Use P = I × I × R to calculate the output power under different external loads. Figure 5 b is the instantaneous output power peak of PFPN-TENG, and its maximum output peak power is 0.61 W, corresponding to a power density of 244 Wm -2 , the matching resistance value is 7MΩ.

[0107] Utilizing the contact-separation mode PFPN-TENG, it can be applied to the collection and conversion of mechanical energy such as vibration in the environment, such as raindrop energy, wave energy, human body movement mechanical energy, etc., to power small energy electronic components, and its electrical output power can light up commercial LED lights.

[0108] Comparative Example 1

[0109] PVDF film is a common industrial transparent film with an average thickness of 30μm.

[0110] Comparative Example 2

[0111] PVDF electrospun solid nanofiber membrane;

[0112] The preparation method is the same as that of Example 1, except that the FEPNPs concentration of the PVDF / FEPNPs spinning emulsion is adjusted to 0 wt % and the spinning humidity is 30%.

[0113] Comparative Example 3

[0114] PVDF porous fiber membrane;

[0115] The preparation method is the same as that of Example 1, except that the FEPNPs concentration of the PVDF / FEPNPs spinning emulsion is adjusted to 0 wt % and the spinning humidity is 70%.

[0116] Comparative Example 4

[0117] FEP film is a common industrial transparent film with an average thickness of 30μm.

[0118] Comparative Example 5

[0119] PTFE film is a common industrial transparent film with an average thickness of 30μm.

[0120] Comparative Example 6

[0121] PVDF / FEPNPs spinning solid fiber membrane;

[0122] The preparation method is the same as that of Example 1, except that the spinning humidity condition of the PVDF / FEPNPs spinning emulsion is adjusted to 30 wt %.

[0123] Comparative Example 7

[0124] PVDF / FEPNPs composite spinning PVDF coated porous fiber membrane;

[0125] The preparation method is the same as that of Example 1, except that the spinning humidity condition of the PVDF / FEPNPs spinning emulsion is adjusted to 70 wt %.

[0126] Experimental Example 1: Comparison of PFPN triboelectric properties

[0127] The friction layer 1 in the contact-separation mode PFPN-TENG of Example 1 was adjusted to the fiber membranes described in Comparative Examples 1-7 respectively, and other conditions remained unchanged, and the electrical performance output test was compared with the contact-separation mode PFPN-TENG.

[0128] The short-circuit current, charge transfer amount, open-circuit voltage, BET specific surface area and SEM morphology of electrospun fibers of the tested control TENG are shown in Figure 2. Figure 6 and Figure 7 .

[0129] like Figure 6 As shown, the electrical output performance of the PFPN-TENG is much better than that of the TENG electrical output of various friction negative layers in the above-mentioned comparative examples 1-7. The PFPN-TENG has a more excellent electrical output performance, indicating that the PFPN film prepared by the present invention has a significant improvement in the output voltage of the TENG, and the prepared PFPN film has excellent friction negative characteristics. Figure 6 It can be seen that the optimal output performance of PFPN-TENG (372μA, 0.735μC) is significantly better than that of commercial FEP film (252μA, 0.493μC) and commercial PTFE film (267μA, 0.517μC), and the surface charge density is increased by 49.1% and 42.2% compared with that of FEP film and PTFE film, respectively.

[0130] The structure of the nanofiber membrane is adjusted by controlling the humidity, thereby preparing composite nanofiber membranes with different fiber structures. Figure 7 Figure 2 is the SEM images of PVDF nanofiber membrane and PVDF / FEPNPs composite nanofiber membrane prepared at relative humidity of 30% and 70%. Figure 7 a, Under low humidity of 30%, the surface of electrospun nanofibers is smooth and the fiber is solid with no pores inside; under humidity of 70%, the surface of the obtained nanofibers is rough and the fiber is full of nanopores ( Figure 7 b). For pure PVDF materials, the commercial PVDF membrane has the lowest output; while the PVDF fiber membrane, due to the increase in effective contact area, produces a high triboelectric charge density, resulting in a higher power generation output. Compared with the PVDF membrane, the short-circuit current increased by 173.1% and 231.6% respectively ( Figure 6 ). However, limited by the triboelectric negative characteristics of PVDF, the electrical output performance of the pure PVDF material layer cannot be compared with that of the commercial FEP and PTFE layers. Comparative Example 2 and Comparative Example 6 have very similar specific surface areas, but show huge differences in triboelectric output. The output performance of the PVDF / FEPNPs nanofiber membrane-based TENG is significantly higher than that of the pure PVDF nanofiber membrane, which indicates that the addition of FEPNPs with high triboelectric properties to PVDF nanofibers can also improve the TENG power. In addition, it can be observed that the PFPN membranes in Comparative Example 6, Comparative Example 7 and Example 1 have the same material composition, but their power generation output is very different. The electrical output of Comparative Example 7 prepared under high humidity conditions is sharply lower than that of the PFPN membrane (short-circuit current is 67.1%, and the amount of transferred charge is 68.0%). The reason for this sharp drop is that the specific surface area is increased from 8.94m 2 g-1 reduced to 3.91m 2 g -1 , corresponding to a decrease of 44.2% ( Figure 6), and in Comparative Example 7, the high negative triboelectric FEP nanoparticles are completely coated with PVDF ( Figure 7 d). This shows that the distribution of FEPNPs in the composite nanofiber membrane has a great influence on the triboelectric properties of the PVDF / FEP NPs composite nanofiber membrane. The tribological properties of the composite PVDF / FEP NPs nanofiber membrane are not only affected by the specific surface area, but also by the composite nanofiber structure, especially the distribution of FEPNPs. This is mainly because the addition of FEP NPs increases the number of nanopores and enhances the friction polarization of the fiber. Embedding nanoparticles in the outer layer of the fiber is conducive to increasing the surface friction charge density and specific surface area, thereby effectively improving the friction point performance of the friction point material. The prepared PFPN membrane of the present invention has a good microcapacitor structure, improves the overall capacitance of the film, and significantly increases the amount of friction transfer charge.

[0131] Example 2

[0132] Verify the influence of the FEPNPs content ratio in PVDF / FEPNPs on the power generation performance of PFPN-TENG.

[0133] Based on the PFPN membrane preparation steps, the content ratio of FEPNPs in PVDF / FEPNPs was adjusted to 0wt%, 12.5wt%, 20wt%, 27.5wt%, 33.33wt%, 38.5wt%, 45wt%, 50.5wt%, 55wt% and 60wt%, and other conditions remained unchanged.

[0134] Figure 8 a shows the test results of the effect of FEPNPs content in the porous nanofiber membrane prepared by the present invention on the short-circuit current and the amount of transferred charge output by PFPN-TENG power generation.

[0135] Since the tribo-negativity of PVDF / FEPNPs is affected by the high polarity of FEPNPs, it is necessary to evaluate the effect of FEPNPs level on the power generation output of PFPN-TENG. The experimental results show that as the mass percentage concentration of FEPNPs in the electrospun nanofibers increases from 0% to 45%, the short-circuit current and the amount of transferred charge of the electrospun nanofibers gradually increase. This improvement, which is faster than the linear growth, can be attributed to the increase of high polarity functional groups in FEPNPs and the increase in the specific surface area of ​​the negative nanocomposite tribo-negative nanofiber film. When the concentration of FEPNPs increases to 45-50wt%, the short-circuit current and the amount of transferred charge reach the maximum value. The addition of FEPNPs increases the electronic functional groups of -CF2-CF2- and -CF3, which makes the PVDF / FEPNPs electrospun nanocomposite fibers have strong electron capture ability. As the FEPNPs content increases from 50%wt% to 60%wt%, the short-circuit current and the amount of transferred charge decrease. This may be due to the aggregation of high-content FEPNPs in the PVDF matrix, which hinders the interaction between nanocomposite nanofibers and causes fiber damage, resulting in a decrease in short-circuit current output.

[0136] Example 3

[0137] Verify the influence of PFPN film thickness on the power generation performance of PFPN-TENG.

[0138] The thickness of the PFPN film was adjusted to 12μm, 20μm, 35μm, 55μm, 65μm, 85μm and 115μm, and the others remained unchanged.

[0139] Figure 8 b is the output voltage of the PFPN-TENG assembled with the PFPN film (thickness of 12μm, 20μm, 35μm, 45μm, 55μm, 65μm, 85μm and 115μm) prepared by the present invention. It shows the dependence of the triboelectric output of the PFPN-based TENG on the increase of the thickness of the PFPN film. With the increase of the thickness of the PFPN film, the short-circuit current and the total amount of transferred charge increase almost linearly, reaching the maximum value at a thickness of 45μm, and then begin to decline. The increase in the thickness of the triboelectric layer is not only conducive to full contact with the object, but also can increase the charge storage space, thereby reducing the repulsion between the internal negative electrons, thereby reducing the triboelectric charge leakage loss caused by electrode exposure.

[0140] Example 4

[0141] Verify the fully fiber-permeable multilayer thin film PFPN-TENG based on PFPN membrane and its motion sensing application.

[0142] In order to demonstrate the responsiveness of the full-fiber breathable PFPN-TENG to various human body movements, the Vos electrical signal was measured in air and water, and the voltage signals of different motion forms (such as striking, twisting, and folding) were analyzed. The full-fiber breathable PFPN-TENG was installed on the human finger joints, and the voltage signal waveform was generated by repeated bending and straightening of the fingers, such as Fig.10 shown.

[0143] First, there is no friction charge on the two friction layers. It takes several motion cycles to generate enough friction charge, regardless of the air ( Fig.10 a) Still in the water ( Fig.10 b), the signal peak value increases from 0V to 5.1V. The full-fiber breathable PFPN-TENG has a fast response speed during finger movement, a strong voltage signal waveform, no noise, and no need for signal post-processing. Fig.10 As shown in a, when the finger is bent at the same amplitude and frequency, a stable voltage output signal is generated ( Fig.10 aⅡ), as the finger flexion movement gradually increases, increase the finger joint flexion from 76° to 100° ( Fig.10 aⅢ), the voltage signal peak gradually increases. The voltage signal also shows a corresponding lower frequency ( Fig.10 aⅣ). The magnitude of the voltage signal is proportional to the flapping force and deformation rate, and the signal frequency fully reflects the movement frequency. As the bending force of the finger joints continues to increase, the peak value of the voltage signal further increases to 5V. Underwater ( Fig.10 b), the all-fiber breathable PFPN-TENG has good waterproof effect and shows excellent voltage signal, with the output voltage peak reaching 4.7V. In addition, small motion disturbances are also reflected in the small peak of the voltage signal, that is, the small bending movement of the finger when it is bent or extended. The all-fiber breathable PFPN-TENG device was subjected to single-point pressing and folding movements, and the corresponding output signals were tested, such as Fig.10 c, Fig.10 d. The full-fiber breathable PFPN-TENG was repeatedly tapped with fingers, and the output voltage was as high as 4.7V. The voltage signal of the full-fiber breathable PFPN-TENG reached 5.1V when it was folded and deformed. Therefore, installing the full-fiber breathable PFPN-TENG on clothes at the elbows, wrists, shoulders, knees, underarms and elbows of the human body can not only collect the mechanical energy of human movement, but also monitor the physiological movement of the human body in a self-powered manner, providing a good candidate for self-powered sensors in real-time monitoring applications.

[0144] Example 5

[0145] Verification of the flexible solid-liquid contact PFPN-TENG in independent layer mode and its application in wave energy generation

[0146] Fig.12 The flexible solid-liquid contact PFPN-TENG collects water wave energy for real-time monitoring and power supply of the marine environment. In order to study the electrical output of the solid-liquid contact PFPN-TENG, a water wave energy harvesting system ( Fig.12 a). Fig.12 b is a photo of the prepared flexible solid-liquid contact PFPN-TENG device, which is fixed on the tank wall. A wave-making pump fixed on the opposite side of the tank wall generates periodic water waves with a frequency of 1.3 Hz and a wave height of ~120 mm. When the waves periodically rise and fall on the surface of the solid-liquid contact PFPN-TENG, the short-circuit current output of the solid-liquid contact PFPN-TENG is shown in Figure 2. Fig.12 As shown in Figure c, the output current short-circuit current peak can reach 41.8μA. Fig.12 d depicts the dependence of the peak power on the load resistance. When the external resistance changes in the range of 1 kΩ-100 MΩ, the TENG output voltage increases from 0.35 V to 322 V, while the load current decreases from 38.8 μA to 9.8 μA. Fig.12 As shown in Figure 5, the peak output power of the flexible thin film solid-liquid contact PFPN-TENG reached 6.41 mW when the load resistance was 14 MΩ, and the average output power was 1.214 mW. By summing up the volumes of the various components of the compact multilayer thin film structure solid-liquid contact PFPN-TENG, it was found that the total volume of the flexible solid-liquid contact PFPN-TENG device was only 2.231 × 10 -6 m -3 The average volume power density of the flexible solid-liquid contact PFPN-TENG device is as high as 544.1 Wm -3 Then, the flexible solid-liquid contact PFPN-TENG charges the 680μF capacitor and provides energy for the TDS water quality monitoring pen. Fig.12 f, when the capacitor is charged to 3.75 V after 243 s, the TDS water quality monitoring pen starts to work and displays the water quality parameters of the measured liquid. Therefore, we believe that the developed flexible solid-liquid contact PFPN-TENG can be used as an ideal power source for real-time self-powered hydrogeological and environmental monitoring in offshore areas by harvesting seawater wave energy.

[0147] The present invention provides a method for preparing a friction nanogenerator material of a superhydrophobic PFPN membrane. The method is simple, and the obtained superhydrophobic nanocomposite porous fiber membrane material has uniform components, high porosity, strong friction polarity, good air permeability and surface hydrophobicity, good waterproofness and excellent triboelectric properties. Applying the superhydrophobic PFPN membrane to the friction nanogenerator can improve the microcapacitor structure of the material, increase the friction charge transfer amount, and thus improve the output performance of the nanogenerator.

[0148] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a triboelectric material of nanoporous composite fibers, characterized in that: The steps include: Adding polyvinylidene fluoride and perfluoroethylene propylene copolymer nanoparticles into a mixed solvent of N,N-dimethylacetamide / acetone, and mixing them evenly to obtain a polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion; The triboelectric material is obtained by electrostatically spinning the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion.

2. The preparation method according to claim 1, characterized in that: The perfluoroethylene propylene copolymer nanoparticles account for 0-65wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion; The polyvinylidene fluoride accounts for 35-100wt% of the mass percentage of the polyvinylidene fluoride / perfluoroethylene propylene copolymer nanoparticle spinning emulsion.

3. The preparation method according to claim 1, characterized in that: The particle diameter of the perfluoroethylene propylene copolymer nanoparticles ranges from 100 nm to 100 μm; The average molecular weight of the polyvinylidene fluoride is in the range of 100,000 to 1.8 million.

4. The preparation method according to claim 1, characterized in that: The perfluoroethylene propylene copolymer nanoparticles are added to a mixed solvent of N,N-dimethylacetamide / acetone, comprising: Perfluoroethylene propylene copolymer nanoparticles are added to a mixed solvent of N,N-dimethylacetamide / acetone, and magnetic stirring is performed for 1-10 hours.

5. The preparation method according to claim 1, characterized in that: Adding polyvinylidene fluoride to a mixed solvent of N,N-dimethylacetamide / acetone includes: Add polyvinylidene fluoride to the N,N-dimethylacetamide / acetone mixed solvent, heat in a water bath with magnetic stirring, the stirring time is 1-10 hours, and the heating temperature is 40-60°C.

6. The preparation method according to claim 1, characterized in that: The parameters of the electrospinning are set as follows: spinning voltage 5-25 kV, roller receiving distance 15-25 cm.

7. A triboelectric material of nanoporous composite fibers obtained by the preparation method according to any one of claims 1 to 6.

8. A friction nanogenerator using the triboelectric material of the nanoporous composite fiber according to claim 7.

9. The triboelectric nanogenerator according to claim 8, characterized in that: It comprises a negative friction layer obtained by cutting the triboelectric material according to claim 7 and pasting it on the surface of a conductive material; Wherein, the thickness of the negative friction layer ranges from 0.005 to 0.40 mm.

10. Use of the triboelectric material according to claim 7 in a motion sensing device or solid-liquid contact power generation based on triboelectric charging.

Citation Information

Patent Citations

  • High-molecular polymer fibrous membrane with through hole structure and preparation method and application thereof

    CN110923954A

  • Sound energy collection power generation device and manufacturing method thereof

    CN113612405A

  • Friction nanometer generator, power generation method and flexible sensor

    CN115765518A

  • Electrostatic perfluoropolymer fiber membrane, preparation method and application

    CN116815416A

  • Combined type vibration energy collecting device

    CN118677204A

Cited By

  • Microcrystalline cellulose triboelectric composite film, preparation method thereof and triboelectric nano-generator

    CN120441885A

  • Composite hydrophobic fiber membrane based on friction nano-generator and preparation method of composite hydrophobic fiber membrane

    CN120625262A